Eksistensi Advokat dalam Penyelesaian Sengketa Perdata melalui Mediasi - Wika Yudha Shanty (University of Merdeka Malang, 2023)
The existence of mediation is a very good step in resolving disputes between the two parties to reach an agreement by not relying on winning and losing. In Indonesia, the regulations regarding mediation are regulated in the provisions of Article 130 HIR and 145 RBg, which later these articles were made effective through Supreme Court Regulation (Perma) Number 1 of 2016 concerning Mediation Procedures in Courts. The implementation of mediation carried out by the parties often ends in a stalemate, meaning that the two parties fail to reach an agreement to reach peace so that the case will be examined and decided by the court through examination and judge's decision (op tegenspraak). The legal issue discussed in this study is how advocates practice in directing parties to resolve disputes through mediation. This study uses normative legal research methods. With the following results; an advocate should reduce his selfishness to not only think about the benefits of his client but also think about the interests of other parties so that an agreement is reached and get the best middle ground for both parties. This is the main goal of successful mediation, namely a win win solution. Furthermore; In providing legal services in the mediation process, an advocate must maintain and maintain the values that exist in each of the parties. These values are religious values, moral values, ethical values and a sense of justice towards the rights and obligations of both parties.